Meninjau Implementasi Work From Home sebagai Strategi Motivasi Kinerja Aparatur Sipil Negara - Kezsya Tesalonika; Ihsan Dailami Yazid; Putri Arsa Dynanty (Jurnal Ilmiah Wahana Pendidikan, 2023)
The implementation of Work From Anywhere (WFA) is a valuable learning outcome from the implementation of Work From Home (WFH). Within the WFA framework, employee motivation is the main aspect that is considered through the application of flexible work methods anywhere or anytime to trigger the desire of employees to work optimally by minimizing boredom. Writing is done using the Narrative Policy Analysis (NPA) method as an analytical tool to explore insights about government policies based on empirical evidence obtained from secondary data. The research results show that in the implementation of WFA, the aspect of flexibility is the key to increasing employee motivation. Many positive impacts arise but are not spared from this method also has its negative sides which can harm the organization so several efforts are needed such as properly planned flexibility arrangements so that these negative impacts can be overcome.